2020
DOI: 10.1016/j.anr.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Needs of Mothers with Infants in the Neonatal Intensive Care Unit: A Qualitative Secondary Analysis

Abstract: Mothers of infants hospitalized in neonatal intensive care units (NICUs) need to be recognized as essential partners of the care team as their presence and involvement are key to infants' health and developmental outcomes. Addressing mothers' perceived needs is beneficial for the improvement of supportive nursing care; however, little qualitative research on their unmet needs has been conducted in South Korea. This study assessed mothers' perspectives on their NICU experiences and their unmet needs within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
5
0
7
Order By: Relevance
“…Mothers in the standard care group did not describe the same feelings of support. This perceived lack of support from healthcare providers is consistent with other studies ( Hassankhani et al, 2020 ; Kim, 2020 ; Sigurdson et al, 2020 ; Wreesmann et al, 2021 ) and may place greater responsibility on mothers to navigate on their own a longer and more circuitous journey to home. To improve the quality of care in all NICUs, future research is needed to better understand the components of AB-FICare™ that contribute to reciprocal trust and maternal feelings of support and empowerment in the care of their preterm infant.…”
Section: Discussionsupporting
confidence: 87%
“…Mothers in the standard care group did not describe the same feelings of support. This perceived lack of support from healthcare providers is consistent with other studies ( Hassankhani et al, 2020 ; Kim, 2020 ; Sigurdson et al, 2020 ; Wreesmann et al, 2021 ) and may place greater responsibility on mothers to navigate on their own a longer and more circuitous journey to home. To improve the quality of care in all NICUs, future research is needed to better understand the components of AB-FICare™ that contribute to reciprocal trust and maternal feelings of support and empowerment in the care of their preterm infant.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have pointed out that parentechild skin contact could enhance parentechild connection. Mothers' participation in caring for newborns and breastfeeding can help mothers feel capable and confident about fulfilling maternal responsibilities [7]. In this study, new finding an in-depth investigation further showed that the timing of the skin-to-skin contact was the turning point in recognizing their maternal identity.…”
Section: Discussionmentioning
confidence: 55%
“…For example, there may be a lack of empathetic communication from medical staff, limited parentechild contact due to the separation from the infants, fear of getting close to the babies when visiting, self-blaming, and emotional crying. These mothers rarely receive proper assistance and timely support from the medical team [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It may be or must be too hard for one nurse to care for several babies properly at once." (South Korea, hospital)[51] "What made me sad is ... you will find your baby there ... not taken care of ... If you happen not to go to the unit because you were not feeling well, by the time you go there to check on her, you will find her in the same sheets and the nappy not changed."…”
mentioning
confidence: 99%